Experimental Analysis of Nano and Engineering Materials and Structures Proceedings of the 13th International Conference on Experimental Mechanics, Alexandroupolis, Greece, July 1-6, 2007 - Gdoutos, E.E (Springer Netherlands : Imprint: Springer, 2007)
ICEM13 focused on all aspects of experimental mechanics of solids with emphasis on mechanical characterization and testing at the micro and nano scale levels. The technical program of ICEM13 was the product of hard work and devotion of more than 100 world leading experts. This volume contains two-page abstracts of the 482 papers presented at ICEM13. The accompanying CD contains the full length papers. The abstracts of the fifteen plenary lectures are included in the beginning of the book. The remaining 467 abstracts are arranged in 23 tracks and 28 special symposia/sessions with 225 and 242 abstracts, respectively. The papers of the tracks have been contributed from open call, while the papers of the symposia/sessions have been solicited by the respective organizers. The volume contains the latest research work of renowned experts in experimental analysis of engineering materials and structures and is useful for students, engineers and researchers who want to get an integrated picture of the recent developments in the area of experimental mechanics.